2022
DOI: 10.1007/s44192-022-00004-3
|View full text |Cite
|
Sign up to set email alerts
|

Men are the main COVID-19 transmitters: behavior or biology?

Abstract: Background COVID-19 has affected millions of people worldwide. Clinical manifestations range from severe cases with lethal outcome to mild or asymptomatic cases. Although the proportion of infected individuals does not differ between sexes, men are more susceptible to severe COVID-19, with a higher risk of death than women. Also, men are pointed out as more lax regarding protective measures, mask wearing and vaccination. Thus, we questioned whether sex-bias may be explained by biological pathwa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…The focus was on individuals in intimate relationships, specifically couples (n=47), who either had symptomatic COVID-19 (SARS-CoV-2 PCR positive) or had not (SARS-CoV-2 PCR negative spouses). Among the infected participants, the majority exhibited mild symptoms (n=40) and were predominantly male, supporting other studies that suggested men were more prone to symptomatic presentations of COVID-19 than females during the first outbreak (2020) of the disease ( 36 , 37 ). Here, our results indicate that both SARS-CoV-2 infected and uninfected individuals exhibit similar levels of IgG antibodies against the RBD portion of endemic coronaviruses.…”
Section: Discussionsupporting
confidence: 79%
“…The focus was on individuals in intimate relationships, specifically couples (n=47), who either had symptomatic COVID-19 (SARS-CoV-2 PCR positive) or had not (SARS-CoV-2 PCR negative spouses). Among the infected participants, the majority exhibited mild symptoms (n=40) and were predominantly male, supporting other studies that suggested men were more prone to symptomatic presentations of COVID-19 than females during the first outbreak (2020) of the disease ( 36 , 37 ). Here, our results indicate that both SARS-CoV-2 infected and uninfected individuals exhibit similar levels of IgG antibodies against the RBD portion of endemic coronaviruses.…”
Section: Discussionsupporting
confidence: 79%
“…Participants included men from 7 geographical regions: Africa (83), Central America (20), North America (8), South America (110), Asia (34), Europe (50), and Oceania (2). In terms of nationalities, 65 different countries were represented: Germany (6), Argentina (29), Angola (14), Algeria (1), Australia (2), Belgium (1), Benin (5), Bolivia (4), Cape Verde (10), Canada (2), Chile (13), China (16), Colombia (14), the Ivory Coast (1), Costa Rica (5), Cuba (1), Croatia (1), Egypt (1), El Salvador (3), Ecuador (4), Spain (2), USA (3), Finland (1), France (8), Ghana (4), Guangdong (1), Guatemala (1), Guinea-Bissau (17), Greece (1), Haiti (5), Honduras (2), India (2), England (4), Iran (1), Ireland (3), Israel (2), Italy (12), Japan (2), Mali (1), Malaysia (1), Morocco (1), Mexico (3), Mozambique (11), Nigeria (4), Norway (1), Palestine (2), Pakistan (1), Paraguay (4), Peru (19), Portugal (4), the Dominican Republic (3), the Republic of the Congo (1), Russia (1), São Tomé and Príncipe (3), Senegal (7), Serbia (1), Syria (3), Switzerland (3), Taiwan (1), Togo (1), Turkey (1), Ukraine (1), Uruguay (8), Uzbekistan (1), and Venezuela (15).…”
Section: Resultsmentioning
confidence: 99%
“…This theory aims to achieve cultural care production, considering cultural practices consistent with the values and beliefs of the populations being assisted in their environments [6]. This theoretical framework can contribute to specialized healthcare, with qualified nursing and healthcare professionals addressing patients' unique demands and needs [8,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A diferença observada neste estudo pode ser explicada pelo fato de homens se preocuparem menos com a saúde [15][16][17] , ou seja, possivelmente, a quantidade de casos positivos de mulheres foi maior porque elas buscam mais o atendimento do sistema de saúde e, por consequência, realizaram mais testes diagnósticos. Além disso, pesquisa realizada com 1.744 casais brasileiros que moravam juntos e um dos cônjuges apresentou teste positivo para a doença constatou que o homem era o primeiro (casais em que ambos foram contaminados) ou o único contaminado (casais em que apenas um membro ficou doente) em aproximadamente 60% dos casos 18 .…”
Section: Resultsunclassified